(untitled) - Greenberg, Jerrold S. (Boston, Mass., 2008)
This engaging and easy-to-read text helps students identify, understand, and combat the stressors that most affect their lives. In an informal, anecdotal style, author Jerrold Greenberg discusses the latest research findings on the physical, psychological, sociological, and spiritual aspects of stress, as well as the appropriate coping skills.
Keywords: Stress (Psychology),Stress (Physiology),Stress management,Stress (Psychology),Sự căng thẳng; Prevention